Pengaruh Proses Rekrutmen Dan Seleksi Terhadap Kinerja Pegawai Binnar School - Vinny Alfanencia Yoastita; Achmad Daengs GS (Universitas 45 Surabaya, 2025)
This study aims to determine the influence of the recruitment and selection process on employee performance at Binar School Surabaya. This study is a quantitative study with a population and sample of 30 respondents, namely teachers and staff at Binar School. Data collection using questionnaires, and data analysis techniques using multiple linear regression assisted by SPSS. The results of the study indicate that the recruitment process has a significant negative effect on employee performance partially, selection has a positive and significant effect on employee performance partially, the recruitment and selection process has a positive and significant effect on employee performance simultaneously.